Refections on electoral violence in Nigeria - Karim, Adegboyega A. (Ibadan : John Archers, 2014)
The book focuses on the dynamics and nuances of electoral violence in Nigeria. It analyses the issues and offers policy recommendations towards preventing and transforming electoral violence in Nigeria.
Includes bibliographical references and index.
oif 16/07/2018
Loans
Keywords: Violence; Elections; Politics and government; Violence -- Prevention; Nigeria